ENHANCING ESL LEARNING THROUGH MUSIC: BOOSTING ENGAGEMENT AND LANGUAGE PROFICIENCY - Lali Tavadze; Natia Katamadze; Ivdit Diasamidze (International Journal of Innovative Technologies in Social Science, 2025)
This paper explores the cognitive, linguistic, and emotional benefits of integrating music into language learning and deals with the ways songs can be used in ESL classrooms to motivate students to learn English and enhance their involvement. Integrating songs in teaching/learning process can result in killing two birds with one stone as songs enhance learners’ skills in listening (by exposing learners to natural rhythm, intonation, and diverse accents), speaking (by introducing colloquial language, idioms, and phrasal verbs, which students may not encounter in traditional textbooks), reading (by improving comprehension and facilitating the identification of words and phrases in real-life contexts) and writing (by encouraging creative expression, with opportunities for writing). Songs can be used in various ways based on teachers’ goals and objectives taking students’ needs into consideration. Through this creative approach students acquire new vocabulary, grammar structures, master pronunciation, stress patterns, intonation. They can be used as language tasks, focusing on a particular material and can be adapted and tailored to specific teaching objectives, to suit the specific purpose a teacher might wish to teach. Songs provide a relaxing break for both students and teachers, turning routine classroom activities into enjoyable, fun experiences. Emotional engagement through music enhances motivation, reduces learning anxiety, and strengthens the emotional connection to language, making the learning experience more memorable.